Statistical analysis of metallurgical industry enterprises in Russia ("Journal "U". Economy. Management. Finance.", 2025)
The article presents a detailed statistical analysis of enterprises in the Russian metallurgical industry, covering key indicators such as the number of enterprises, the number of employees in the industry, the level of nominal wages, balanced financial results and profitability. The authors identify the main trends in the development of the industry, analyze its contribution to the country's economy and determine its importance as one of the most important for sustainable growth and industrial development. The study makes it possible to assess the current state of the metallurgical industry, identify problems and prospects for its further development, which makes the article relevant for economists, analysts and specialists in the field of industrial policy.
Keywords: economic processes; types of economic activity; metallurgical production; nominal wages; financial result of enterprises; profitability of products; return on assets